Editor's Choice- Impact of insulin-treated diabetes on cardiovascular outcomes following high-risk myocardial infarction. Issue 3 (1st April 2019) - Rossello, Xavier; Ferreira, João Pedro; McMurray, John J V; Aguilar, David; Pfeffer, Marc A; Pitt, Bertram; Dickstein, Kenneth; Girerd, Nicolas; Rossignol, Patrick; Zannad, Faiez; ,
Abstract: Background: Diabetes is associated with poor cardiovascular outcomes, and insulin-treated patients usually have a worse prognosis than non-insulin-treated subjects. The relationship between insulin treatment and outcomes in high-risk myocardial infarction patients has not been described in a large dataset. Methods: To investigate the association between insulin-treated diabetes and long-term cardiovascular outcomes in patients with high-risk myocardial infarction, we used adjusted Cox models to compare cardiovascular mortality and hospitalisation among 28, 771 patients grouped by diabetes status and insulin treatment from four randomised clinical trials (VALIANT, EPHESUS, OPTIMAAL, CAPRICORN) of acute myocardial infarction complicated by heart failure and/or left ventricular systolic dysfunction. Results: After an approximately 2-year follow-up, patients with no diabetes (21, 386 subjects, 74.3%), non-insulin-treated diabetes (4977 patients, 17.3%) and insulin-treated diabetes (2409 subjects, 8.4%) had an incremental yearly mortality risk (15.8%, 21.3% and 28.1%, respectively). Insulin-treated diabetes patients presented with a higher cardiovascular burden and comorbidities. After adjustment for 18 baseline covariates, patients with non-insulin-treated and insulin-treated diabetes were at higher risk of cardiovascular death (hazard ratio (HR) 1.25, 95% confidence interval (CI) 1.13–1.38 and HR 1.49, 95% CI 1.31–1.69, respectively; P for comparison of non-insulin-treated vs. insulin-treated diabetes =0.016) and cardiovascular hospitalisation (HR 1.33, 95% CI 1.25–1.41 and HR 1.16, 95% CI 1.11–1.22, respectively) compared to patients without diabetes. These results remained consistent after further adjustment for medications and left ventricular ejection fraction. Conclusions: Insulin-treated diabetes patients had higher event rates than diabetes patients taking oral treatments and patients without diabetes. However, insulin-treated diabetes patients had more comorbidities and atherosclerotic disease, precluding any causality suggestion between insulin treatment and outcomes. This high-risk population may require specific and/or more intense cardiovascular protective therapies.